Structure, magnetism and colour in simple bis(phosphine)nickel(II) dihalide complexes: an experimental and theoretical investigation - Schultz, Madeleine; Pleßow, Philipp; Rominger, Frank; Weigel, Laura Kathrin (Acta crystallographica. Section C, Structural Chemistry, 2013)
The complex [1,2-bis(di-tert-butylphosphanyl)ethane-κ2P,P′]diiodidonickel(II), [NiI2(C18H40P2] or (dtbpe-κ2P)NiI2, [dtbpe is 1,2-bis(di-tert-butylphosphanyl)ethane], is bright blue-green in the solid state and in solution, but, contrary to the structure predicted for a blue or green nickel(II) bis(phosphine) complex, it is found to be close to square planar in the solid state. The solution structure is deduced to be similar, because the optical spectra measured in solution and in the solid state contain similar absorptions. In solution at room temperature, no 31P{1H} NMR resonance is observed, but the very small solid-state magnetic moment at temperatures down to 4 K indicates that the weak paramagnetism of this nickel(II) complex can be ascribed to temperature independent paramagnetism, and that the complex has no unpaired electrons. The red [1,2-bis(di-tert-butylphosphanyl)ethane-κ2P,P′]dichloridonickel(II), [NiCl2(C18H40P2] or (dtbpe-κ2P)NiCl2, is very close to square planar and very weakly paramagnetic in the solid state and in solution, while the maroon [1,2-bis(di-tert-butylphosphanyl)ethane-κ2P,P′]dibromidonickel(II), [NiBr2(C18H40P2] or (dtbpe-κ2P)NiBr2, is isostructural with the diiodide in the solid state, and displays paramagnetism intermediate between that of the dichloride and the diiodide in the solid state and in solution. Density functional calculations demonstrate that distortion from an ideal square plane for these complexes occurs on a flat potential energy surface. The calculations reproduce the observed structures and colours, and explain the trends observed for these and similar complexes. Although theoretical investigation identified magnetic-dipole-allowed excitations that are characteristic for temperature-independent paramagnetism (TIP), theory predicts the molecules to be diamagnetic.
Gesehen am 26.07.2021